Study on optical fiber multi-parameter sensor - Tongyu LIU; Zhen LI; Xiangjun MENG; Lin ZHAO; Fuqi WANG; Guofeng DONG; Jiqiang WANG (Tongxin xuebao)
Based on the principle of fiber Bragg grating detection,an optical fiber sensor for detecting wind speed and temperature and humidity in underground space was designed.The designed optical fiber wind speed sensor was based on the thermal flow detection method,which has high sensitivity to low wind speed.For the speed rising from 0 to 0.5 m/s,the wavelength variation is about 800 pm.For the demodulator with sensitivity of 1 pm,the speed resolution is 0.7 mm/s.Fiber optic humidity sensor was fabricated by uniform surface coating of FBG element in polyimide solution,and detection sensitivity of 4.2 pm/% RH was achieved with accuracy less than ± 3% RH.